Critical analysis of objectivity on RH Bill news report using gauthier's propositions. - Salvador, Bernadette Anne
The purpose of this study is to determine whether news reports about reproductive health bill or the RH bill in the three daily broadsheets in the Philippines namely: Philippine Daily Inquirer, Manila Bulletin and the Philippine Star are objective or not using the five propositions of Gauthier. Interview fromt he news writers of RH Bill was conducted and the news reports that they wrote were the subjects of the study. Results showed that news reports about RH bill are objective but have limitations. The three daily broadsheets failed to present straight news reports consistently because of the journalist's different writing styles. One major predicament for the news writers was the availability of sources wherein they tend only one side in their stories mainly because sources are not always available. Lastly, the external factors contributed to the limitations for presenting objective news reports because their selection of topic and content of their reports landed heavily on their beliefs which made their news reports as biased. Although these criteria were not met, most of the journalists still agreed that it is still possible to attain objectivity if they are just going to write their news reports in an ethical manner which was supported by Gauthier's statement that objectivity's essential concern is the primary, fundamental relationship between the journalist and the facts that he or she reports, which is to say, the way the journalist process information.